Liposomes for vaccine delivery against infectious bursal disease in chickens - Wahab, Mukminah Sakinah (2016)
Application of liposomes may help to enhance vaccine delivery process. Infectious bursal disease (IBD) is a highly contagious viral disease of chickens which cause immunosuppression and high mortality. Therefore, the objectives of this study were to develop a suitable liposomes for IBD vaccine delivery using a thin lipid hydration method, to determine the safety of the developed liposomes in embryonated specific pathogen free (SPF) chicken eggs and effectiveness of the encapsulation of IBD vaccine in liposomes in commercial broiler chickens. Three experiments were conducted in this study; 1, 2 and 3. In experiment 1, positively charge liposomes consist of three major components of lipids namely; dipalmitoylphosphatidylcholine (DPPC), cholesterol and sterylamine (SA) was successfully prepared. Thin lipid hydration technique was used for preparation of cationic liposomes. The results showed a significant differences (p<0.05) between the particles size of empty cationic liposomes when compared to the size of IBD vaccine with three different mixtures of working seed IBD virus (IBDV) MyHatch UPM93 with cationic liposomes based on ratio; 1:1, 1:2 and 2:1 and identified as Sevac 1, 2 and 3, respectively. The value of zeta potential for the cationic liposomes and Sevac formulations were varying from 17±29.68 mV to 32±21.58 mV. Safety study showed 67% and 33% death of embryo in the liposomes and Sevac 3, but not in other groups. It appears that SA is toxic to the embryonated eggs. In experiment 2, the method of liposomes preparation and safety of the cationic liposomes in SPF embryonated chicken eggs were successfully developed. 1,2-dioleoyl-3-trimethylmmonium propane (DOTAP) was used in the study to replace SA. A 1:1 and 1:2 ratio groups were selected with two types of live attenuated IBDV namely as Se (IBDV of UPM93 seed virus) and Co (IBDV of UPM93 commercial vaccine). Several methods for the preparation of cationic liposomes in the experiment 1 were modified. The results showed that all embryonated SPF chicken eggs in all groups were survived throughout 7 days post inoculation (pi). This further confirmed that SA is toxic to embryonated chicken eggs, whilst DOTAP is safe to be used in preparation of cationic liposomes. In experiment 3, the effects of IBD vaccine and a safe liposomes mixture on the induction of high and protective IBD antibody titre were determined in commercial broiler chickens at hatchery vaccination via subcutaneous route. The study showed that the chickens in all groups did not exhibit any abnormal clinical signs and gross lesions, except atrophy of the bursa of Fabricius at day 28 post vaccination (pv) for IBD, Covac and Sevac groups throughout the experiment. The bursa weight and bursa to body weight ratio were remained unchanged for the IBD, Covac and Sevac groups compared with the Control group except at day 28 pv. The lesion scoring of the bursa of Fabricius was detected as early as 21 days pv in the Covac and Sevac groups compared to the IBD group at 28 days pv. The IBD antibody titre in the Covac and Sevac groups started to increase at day 21 pv compared to the IBD group at day 28 pv. Despite of low dosage of IBDV in the Covac group (2/3) when compared to the IBD group the induction of IBD titre was remained high in the group. This indicated that the encapsulation of IBDV in liposomes could enhance the induction of IBD antibody. In conclusion, this study demonstrated that the application of cationic liposomes can enhance the deliver IBD vaccine to the target organ, the bursa of Fabricius, and induce high and protective level of IBD antibody titre with mild bursal lesion. Hatchery or day old vaccination using MyHatch UPM93 strain either with or without cationic liposomes is effective and could induce high and protective level of IBD antibody against IBDV challenged. These applications will give a new dimension in the field of poultry vaccines and vaccination.